Intergenerational Trade, Longevity, and Economic Growth - Ehrlich, Isaac; Lui, Francis T. (Journal of Political Economy, 1991)
We develop an overlapping-generations model of endogenous growth in which human capital is the engine of growth and the generations are linked through material and emotional interdependencies within the family. Parents invest in their children to achieve both old-age support (care) and emotional gratification, and material support from children is determined through self-enforcing implicit contracts. We show that optimal intergenerational trade can then lead to maximization of growth opportunities. Our model produces a theory of the "demographic transition" linking longevity, fertility, and economic growth. We also show that while population aging may raise the growth rate, an increase in young-age longevity is likely to produce a greater increase in the growth rate and a reduction in the fertility rate in a growth equilibrium. These predictions and the model's implications concerning the behavior of private savings during the takeoff period appear consistent with empirical evidence.